1998
DOI: 10.1128/iai.66.5.2170-2179.1998
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Neutralizing Antipeptide Antibodies to the Enzymatic Domain of Pseudomonas aeruginosa Exotoxin A

Abstract: Burn patients suffer a break in the physical barrier (skin), which, when combined with their generalized state of immunodeficiency, creates an open window for opportunistic infections, mainly with Pseudomonas aeruginosa. Infection of the burn wound has always been a major factor in retardation of wound healing, and sepsis remains the leading cause of death in burn patients. Because studies have shown that topical treatment with antiexotoxin A (ETA) antibodies significantly increases survival in rats infected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Antibodies to the 13 aa within the carboxyl half of peptide 11 were more efficient than antibodies to peptide 11 itself in neutralizing the cytotoxic and enzymatic activities of ETA. In the same study, we identified another synthetic peptide encompassing a region within the translocation domain of ETA (aa 289 to 333), which induced antibodies with moderate ability to neutralize the cytotoxic activity of ETA in vitro (5). Four synthetic peptides encompassing regions within the binding domain of ETA failed to induce ETAneutralizing antibodies (5).…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…Antibodies to the 13 aa within the carboxyl half of peptide 11 were more efficient than antibodies to peptide 11 itself in neutralizing the cytotoxic and enzymatic activities of ETA. In the same study, we identified another synthetic peptide encompassing a region within the translocation domain of ETA (aa 289 to 333), which induced antibodies with moderate ability to neutralize the cytotoxic activity of ETA in vitro (5). Four synthetic peptides encompassing regions within the binding domain of ETA failed to induce ETAneutralizing antibodies (5).…”
mentioning
confidence: 88%
“…In the same study, we identified another synthetic peptide encompassing a region within the translocation domain of ETA (aa 289 to 333), which induced antibodies with moderate ability to neutralize the cytotoxic activity of ETA in vitro (5). Four synthetic peptides encompassing regions within the binding domain of ETA failed to induce ETAneutralizing antibodies (5). In the present study, we examined the potential of neutralizing antipeptide antibodies to confer protection against ETA or infection with an ETA-producing strain of P. aeruginosa in mice.…”
mentioning
confidence: 94%
See 3 more Smart Citations